Empirical research on information and knowledge management in designing: where are we and where do we go from here?. (26th December 2007) - Lauche, Kristina
Research into information and knowledge management in designing needs to take the specific context and challenges of design activities into account, but it should also draw on existing research and theories about how other professionals deal with complex tasks, how they search for solutions and share and develop knowledge in comparable settings. The author's experience of several research projects and a review of recent conferences show that the state of the art is rather piecemeal and rarely founded on existing social science knowledge. This situation is interpreted as pre-normal science in Kuhn's sense and as a result of structural obstacles for interdisciplinary collaboration in the academic world. Since knowledge management is a particularly striking example of the relevance of cognitive, social and organisational aspects of understanding design activity, the paper proposes avenues into the psychological literature with the aim of stimulating well-founded empirical research in this area.